Intertidal burrowing shrimps (Axiidea: Callianassidae, Callichiridae; Gebiidea: Axiannassidae, Upogebiidae) collected along the Brazilian coast - Hernáez, Patricio; Pinheiro, Marcelo Antonio Amaro [UNESP]; Almeida Alves-Junior, Flávio; Santana, William (Taylor & Francis, 2022)
An annotated checklist of the intertidal species of burrowing shrimps of the Brazilian coast is provided from samples collected during latitudinal research expeditions between 2015 and 2018. A total of 1166 specimens of nine species were collected in these expeditions. These species are listed by infraorder and family as follows: Axiidea: Callianassidae (Biffarius botterae), Callichiridae (Audacallichirus mirim, Callichirus corruptus, Lepidophthalmus siriboia, Neocallichirus guara, N. maryae, N. pinheiroi); Gebiidea: Axianassidae (Axianassa australis), Upogebiidae (Upogebia omissa). For each species, the diagnostic features, distribution and habitat are recorded. The taxonomic information is discussed and compared with the information reported in literature for each taxon.
Keywords: Decapoda; ghost shrimps; mud lobsters; south-western Atlantic; Thalassinidae